QUALITATIVE CHARACTERISTICS AND PRINCIPLESOF FINANCIAL REPORTS IN THE CONTEXT OF DISCLOSUREOF INFORMATION ABOUT THE ENTERPRISE AS A SUBJECTOF TAX RELATIONS - Nataliia Shalimova; Halyna Kuzmenko (Izdevnieciba "Baltija Publishing", 2016)
In the article ways of information visibility provision concerning tax relations of the enterprise in the system of accounting and financial report are investigated. It is substantiated that necessity of information disclosure about tax relations of the enterprise is a result of such qualitative characteristic of financial reports as relevance and two principles of its preparation: principle of full presentation and principle of going concern. Contents of separate paragraph in the notes to Annual Financial Reports dedicated to information disclosure about the enterprise as a subject of tax relations is proposed.